The Gut Microbiota in Multiple Sclerosis: An Overview of Clinical Trials. Issue 12 (December 2019) - Schepici, Giovanni; Silvestro, Serena; Bramanti, Placido; Mazzon, Emanuela
Multiple sclerosis (MS) is a chronic, inflammatory, demyelinating, and degenerative disease that affects the central nervous system. A recent study showed that interaction between the immune system and the gut microbiota plays a crucial role in the development of MS. This review reports the clinical studies carried out in recent years that aimed to evaluate the composition of the microbiota in patients with relapsing–remitting MS (RR-MS). We also report what is available in the literature regarding the effectiveness of fecal microbiota transplantation and the role of the diet in restoring the intestinal bacterial population. Studies report that patients with RR-MS have a microbiota that, compared with healthy controls, has higher amounts of Pedobacteria, Flavobacterium, Pseudomonas, Mycoplana, Acinetobacter, Eggerthella, Dorea, Blautia, Streptococcus and Akkermansia . In contrast, MS patients have a microbiota with impoverished microbial populations of Prevotella, Bacteroides, Parabacteroides, Haemophilus, Sutterella, Adlercreutzia, Coprobacillus, Lactobacillus, Clostridium, Anaerostipes and Faecalibacterium . In conclusion, the restoration of the microbial population in patients with RR-MS appears to reduce inflammatory events and the reactivation of the immune system.